2008
DOI: 10.1128/aac.00987-07
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorothioate-Modified Oligodeoxynucleotides Inhibit Human Cytomegalovirus Replication by Blocking Virus Entry

Abstract: Studies in animal models have provided evidence that Toll-like receptor 9 (TLR9) agonists, such as synthetic oligodeoxynucleotides (ODNs) that contain immunostimulatory deoxycytidyl-deoxyguanosine (CpG) motifs (CpG ODNs), protect against a wide range of viral pathogens. This antiviral activity has been suggested to be indirect and secondary to CpG-induced cytokines and inflammatory responses triggered through TLR9 activation. However, few studies have addressed the potential of CpG ODNs as direct antiviral age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…binding inhibition. This phenomenon could be extended to the inhibition of virus entry, as it has been recently shown that human cytomegalovirus, hepatitis C virus, and HIV entry are blocked by phosphorothioate-modified ODNs, regardless of CpG motifs (33)(34)(35)(36). One could therefore take advantage of this to design antiviral vaccines that target virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…binding inhibition. This phenomenon could be extended to the inhibition of virus entry, as it has been recently shown that human cytomegalovirus, hepatitis C virus, and HIV entry are blocked by phosphorothioate-modified ODNs, regardless of CpG motifs (33)(34)(35)(36). One could therefore take advantage of this to design antiviral vaccines that target virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…The cells and supernatants from the antiviral assay were then harvested and disrupted by sonication. The extent of virus replication was subsequently assessed by titrating the infectivity of the supernatants of cell suspensions on either HELFs (for HCMV, adenovirus and VSV) or NIH 3T3 cells (for MCMV) as previously described (Luganini et al, 2008a). Plaques were microscopically counted and the mean plaque counts for each drug concentration were expressed as a percentage of the mean plaque count of the control virus.…”
Section: Antiviral Assaysmentioning
confidence: 99%
“…Real-time quantitative reverse transcription-PCR (RT-PCR) was performed on an Mx 3000 P apparatus (Stratagene) using SYBR Green as a non-specific PCR product fluorescence label as previously described (Caposio et al, 2007b;Luganini et al, 2008a). After HCMV infection and cell treatment, total cellular RNA was isolated using the Eurozol reagent (Euroclone Ltd., United Kingdom) and RNA samples (1 g) were then retrotranscribed at 42°C for 60 min in PCR buffer (1.5 mM MgCl2) containing 5 M random primers, 0.5 mM deoxynucleoside triphosphates, and 100 U Moloney murine leukemia virus reverse transcriptase (Ambion) in a final volume of 20 l. Reverse-transcribed cDNAs (2 l), or water as the control, were then amplified in duplicate using the Brilliant SYBR Green QPCR master mix (Stratagene) in a final volume of 25 l. Primer sequences were as follows: IE1 (sense, 5'-CAA GTG ACC GAG GAT TGC AA-3'; antisense, 5'-CAC CAT GTC CAC TCG AAC CTT-3'); IE2 (sense, 5'-TGA CCG AGG ATT GCA ACG A-3'; antisense, 5'-CGG CAT GAT TGA CAG CCT G-3').…”
Section: Quantitative Viral Nucleic Acid Analysismentioning
confidence: 99%
“…1 thioated substrate have been demonstrated to have antiviral activities by blocking viral entry (Luganini et al, 2008;Matsumura et al, 2009), replication (Torrence et al, 2006), packaging (Giannecchini et al, 2009;Takahashi et al, 2009), translation (Gonzalez-Carmona et al, 2013), and in some cases by targeting microRNA (Gebert et al, 2014;Lanford et al, 2010). Among P = S ONs studied as antiviral compounds, P = S ONs that inhibit HIV-1 infection have attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…These suggested mechanisms include blocking of viral adsorption (Luganini et al, 2008;Wyatt et al, 1994) and/or inhibition of HIV-1-specific enzymes, such as reverse transcriptase (Marshall and Caruthers, 1993;Marshall et al, 1992) or integrase (Jing and Hogan, 1998;Jing et al, 2000). P = S oligodeoxycytidine [poly (SdC) 28 ] interacts specifically with the positively-charged V3 loop of HIV-1 gp120 (Vaillant et al, 2006), possibly resulting in the inhibition of HIV-1 replication.…”
Section: Introductionmentioning
confidence: 99%